Підвищення ергономічності настільної лампи lightmaster de 1142 - Поєдинок, Д. Д.; Довгаль, Д. О. (НТУ ДП, 2022)
У роботі запропонований варіант модернізації конструкції настільного точкового освітлювача з метою підвищення ергономічності виробу. Розроблено та впроваджено в існуючу конструкцію освітлювача поворотний механізм, який забезпечую можливість керування напрямком світлового потоку під час експлуатації.

This article proposes a variant of modernization of the design of a table spot‐light in order to increase the ergonomics of the product. A rotary mechanism has been devel‐oped and implemented in the existing design of the luminaire, which provides the ability to control the direction of light flux during operation.
Increasing the ergonomics of a table lamp lightmaster de 1142
Keywords: настільний освітлювач; ергономіка; поворотний механізм; table light; ergonomics; rotary mechanism; 3D‐model; Inventor